Emotional intelligence and at-risk students - Abdullah, Maria Chong; Lee, Phaik Gaik; Roslan, Samsilah; Baba, Maznah (SAGE Publications, 2015)
This study examined the relationships between emotional intelligence (EI) and the delinquent behavior (DB) of the students. The level of DB reported by the students is categorized under the headings of crime, drugs, vandalism, pornography and sexual behavior, other misbehavior, and dishonesty. Meanwhile, EI is investigated by looking at the level of EI domains, such as self-awareness, self-regulation, self-motivation, empathy, social skills, maturity, and spiritual awareness. Data were gathered from a sample of 300 secondary school students aged 15 to 18 years in Selangor. The schools they attended were selected from the so-called “hardcore schools,” which were identified by Schools Division in the State of Selangor. Two instruments, namely, surveys on the “Behavior of Students” and “Malaysian Emotional Quotient Inventory (R)–Adolescence (MEQI),” were utilized to collect the research data and were analyzed using SPSS 19.0. The data showed that the highest delinquency among the adolescents was misbehavior in school, followed by crime, vandalism, pornography, dishonesty, and drugs. Results also revealed a negative linear relationship between EI (r = −.208, n = 300, p = .001) and DB, implying that adolescents with better EI had lower levels of delinquency. Multiple regression analysis revealed that EI is a significant predictor of DB and self-awareness is the main factor of DB. This study contributes to the knowledge of the importance of EI in understanding DB. EI can be used to identify and discriminate emotional skills among those adolescents who exhibit DB. Addressing the role of EI as a predictor would probably prove to be effective in reducing DB.